Mother Tongue Affecting the English Vowel Pronounciation of Batak Toba Adults - ., Ambalegin; Suryani, M S (KnE Social Sciences, 2018)
The paper focuses on description of mother tongue affecting the Batak Toba adults’ in pronouncing English vowel sounds. This qualitative study used 12 vowel sounds of English. The 40 respondents are 20 to 40 years old originated Batak Toba male and female adults who live in Batam. The techniques of data collection were recording and one-on-one interviewing. The analysis applied the theory of Finegan (2015). The result showed that the respondents could not pronounce the vowel /æ/ as in word mat, almost all of them could not pronounce vowel /3:/ as in the word of bird, the vowel /i:/ as in eat, and vowel /O:/ as in saw. Then, all of the respondents could pronounce the vowel /I/ as in it, /e/ as in get, and vowel /O/ as in dog. Additionally, almost of them could pronounce the vowel /2/ as in word cut and vowel /U/ as in put. Almost all of the respondents could pronounce the word of two /u:/ and half of them could pronounce the word of ago /@/. This phenomenon happened because there is a language contact between Bahasa Indonesia and Batak Toba language. Even though there is no long vowel sounds in Batak Toba language as on Toba’s Surat Batak, the vowel sounds are /2/, /I/, /e/, /U/, and /5/, but In Bahasa Indonesia, there are vowel sounds of /@/ for mereka, bersih and /u:/ for bu. Keywords: Batak Toba, mother tongue, pronunciation, Toba’s Surat Batak, vowel sounds